Halal Awareness and Halal Certification: Its Effect on Customer Loyalty of Mie Gacoan with Celebrity Endorsment as an Intervening Variable - Fahmi Rizal Muhaimin; Mashudi Mashudi (Universitas KH. Abdul Chalim Mojokerto, 2025)
Along with the increasing Muslim population and halal awareness, the halal lifestyle is inseparable from the lives of the world community because halal is no longer just a religious issue but has become a realm of trade and a symbol of global quality assurance, in the end halal products are not only important for Muslims but will be important for non-Muslims as well, so Halal Awareness and Halal Certification are determined as the dependent variables of the study. Mie Gacoan was chosen as the object of research because it is a very popular business in Indonesia and has implemented Islamic Branding with Halal Certification and Digital Marketing with the use of Celebrity Endorsement. This research is important to continue because it can provide consideration for business people in making more innovative, creative and strategic marketing strategy decisions according to location, era and consumer preferences. This research method is quantitative. Non-probability sampling technique. Primary data sources are questionnaires and secondary data from books, journals and relevant websites. The number of samples was determined based on the Cochran formula with the resulting number of 96 samples and increased to 100 samples in the process. The sampling method is purposive sampling. The results showed that the effect of Halal Certification on Customer Loyalty had a significant and accepted effect and the other variables tested in this study did not show a significant effect so that it could not be accepted.